Standardized terminology and nomenclature for respiratory cytology: The Papanicolaou Society of Cytopathology guidelines. Issue 5 (15th March 2016) - Layfield, Lester J.; Baloch, Zubair; Elsheikh, Tarik; Litzky, Leslie; Rektman, Natasha; Travis, William D.; Zakowski, Maureen; Zarka, Matthew; Geisinger, Kim
Abstract : Background: The Papanicolaou Society of Cytopathology has developed a set of guidelines for respiratory cytology including indications for cytologic testing, techniques for cytologic sampling, terminology and nomenclature for respiratory diseases, ancillary testing, and recommendations for postcytologic diagnosis follow‐up and management. Methods: All documents are based on the expertise of the authors, an extensive literature review and discussions of the draft documents at national and international meetings over a 12‐month period. This document selectively presents the results of these discussions and reports a proposed standardized terminology scheme for respiratory cytology that correlates cytologic diagnosis with biologic behavior and patient management. Results: The classification and terminology scheme recommends a six‐tiered system composed of: nondiagnostic, negative, atypical, neoplastic (benign and neoplasms of low malignant potential), suspicious, and positive for malignancy. Conclusion: The scheme recommends statements on specimen adequacy followed by the major classification category and then a subclassification and/or comments section. Each of the six main diagnostic categories is associated with an estimated risk of malignancy. Subsequent documents will propose ancillary testing recommendations, techniques for cytologic sampling, indications for cytologic study and postcytologic diagnosis management and follow‐up recommendations. Diagn. Cytopathol. 2016;44:399–409. © 2016 Wiley Periodicals, Inc.